Wykorzystanie związków fosforynowych w leśnictwie - Tkaczyk, Miłosz; Kubiak, Katarzyna; Nowakowska, Justyna; Oszako, Tomasz; Sawicki, Jacek (Leśne Prace Badawcze, 2016)
Phosphite preparations are now an important alternative in plant protection against new, invasive pathogens of the genus Phytophthora and/or Pythium. It is crucial to intervene when alien, invasive oomycetes are carried to plantations or forest stands and attack fine roots via zoospores. The aim of this paper was to demonstrate the possibility of phosphite application to induce resistance to tree pathogens. Phosphate-based fertilizers have been used successfully in nurseries, where application is relatively easy by means of foliar sprays. The traditional fungicides, which are effective in combating fungi, however, fail to control oomycetes. Instead, they mask the disease, which in turn causes serious damage to seedlings after they have been planted in a suitable environment. Moreover, the number of effective fungicides available for forest plant protection has continued to decrease in the last decade. The effectiveness of the chemicals is reduced due to their frequent use and their similarity in terms of the active compound or the mechanism of action. Given the low diversity of active compounds, it is necessary to monitor the development of resistance of pathogens to fungicides by means of molecular biology (sequencing and quantitative PCR). Minimizing the undesired side effects of chemicals on both, mycorrhizal fungi and pathogens can be achieved by strict adherence to rigorous security measures and, where possible, frequently changing the active compounds to alternatives such as phosphites. The significance of phosphate and phosphite uptake by trees is still a matter of debate, especially under field conditions. Nevertheless, phosphites are environmentally friendly compounds, which constitute an alternative or complement to the traditional chemicals (in accordance with the Directive on Integrated Plant management).